Produção de óleo essencial de Ocimum basilicum L. em diferentes épocas, sistemas de cultivo e adubações - José Magno Q LUZ (Boletín Latinoamericano y del Caribe de Plantas Medicinales y Aromáticas, 2014)
Climatic factors influences the production of active principles of aromatic plants. We evaluated the biomass and essential oil of basil (Ocimum basilicum L.). Basil growns mainly by small farmers seeking to sell their leaves, which can be used fresh, dried, as flavorings or seasonings. The experimental design was completely randomized in a 2x2x2 factorial (growing seasons, environments and different kinds of fertilizers). We analyzed plant height, length and width of leaves, fresh and dry weight, yield and essential oil. Comparing the season and environments, the results showed that the plant height were higher in second season. The fertilization did not significantly influence the development and production of essential oils of basil at the two cropping seasons. The cultivation in winter in a protected environment favored crop development, production and essential oil yield.